Shenshi 紳士 atau Gentry Cina: Sekilas Sejarah dan Profil Kaum Aristokrat Cina pada Zaman Kekaisaran - Waworuntu, Adrianus L.G (UI Scholars Hub, 2012)
In order to comprehend the many aspects of social and cultural historiography of traditional China, it is imperative to recognize who are the main actors. In traditional Chinese society, there is a significant category known as the Chinese gentry, or the shenshi 紳士 in Mandarin. They were known as the Chinese scholar-official class who administered the traditional Chinese dynastic government system since more than two-thousand years ago until the abolishment of the system in 1911. The Chinese gentry emerged from the intellectuals who became officials by going through a special, open-recruited, educational system; a system that enabled every person from any strata in traditional society to enroll. However, their office and titles could not be passed to their offspring through birthright. All ministers, governors, magistrates, intellectuals, poets, men of letters, and also the metropolitan and local informal leaders emerged from this class. Chinese histories in the times of the various dynasties are decorated by the roles and actions of this shenshi.